Juventud y política, La Reforma Universitaria Del 18 - Echazu Higa, María Belén; Dominguez, Inés Lilian; Molina, Laura; Stropa, Germán Alejandro; Zamar, Sergio Agustín (Universidad Nacional de Córdoba. Facultad de Odontología, 2021)
Fil: Echazu Higa, María Belén. Universidad Nacional de Córdoba. Facultad de Odontología; Argentina